KETERAMPILAN MENULIS BAHASA JERMAN SISWA KELAS XI SMAN 2 JOMBANG DENGAN MEDIA VIDEO EASY GERMAN - SATYA CITRA ANJANI, BERLY (LATERNE, 2018)
In German lessons, students not only learn vocabulary and language, but also grammar. Therefore, a medium is needed to develop the writing skills of the students. Are there any difficulties in attributing expressions in German lessons because they differ in writing from other languages? However, there is a learning medium that can overcome the gloominess. Easy German video is an online series that subjects German speakers around the world to authentic language learning materials using audiovisual media. The formulation of this research problem is